SORGA DAN NERAKA SEBAGAI SIMBOL:: KAJIAN BIBLIKA DOKTRIN KRISTEN PROGRESIF DAN IMPLIKASINYA BAGI ORANG PERCAYA - Pattinaja, Aska Aprilano; Octavianus, Jonathan; Wau, Hasanema (Jurnal Teologi RAI, 2025)
This article aims to explore a controversial issue in Progressive Christian thought, specifically the rejection or symbolic interpretation of eschatology, especially concerning the reality of heaven and hell. A review of the literature reveals a research gap in this area because studies on Progressive Christianity tend to focus only on soteriology, bibliology, and apologetics. Using a biblical study method with an exegetical analysis approach and historical-systematic theology, this research finds that the symbolic theological approach often weakens the biblical foundation of God's justice and holiness and clouds the eschatological truth as taught by Jesus and the apostles. Therefore, this article presents a biblical reading that affirms a balance between divine love and justice, demonstrating that the doctrines of heaven and hell are not merely moral constructs but essential parts of the salvation story. The results are expected to enhance the discourse of Indonesian contextual theology by illustrating the limits of progressive hermeneutics in relation to the orthodoxy of the Christian faith.